Ohanian's celebrity endorsers' credibility scale:evaluation and validation in the context of an emerging economy. (1st March 2012) - Gaur, Sanjaya Singh; Tiwari, Shalini Pathak; Bathula, Hanoku
This study is designed to validate Ohanian's (1990) celebrity endorsers' credibility scale in the context of an emerging economy. We used two Indian celebrities as stimuli and collected data from a sample of young Indians who are relatively more susceptible to celebrities' influence. The results support both convergent and discriminant validity for the scale after dropping two of the observed variables. The convergent and discriminant validity of the modified scale was established from a variety of methods, and robust support was found for the same. This study shows that the modified scale can be used in an Indian context as well as in countries similar to India for identifying the most suited celebrity endorser.